Prevalence of Obsessive-Compulsive Disorder and Migraine among University students of big cities of Pakistan: A Cross-Sectional Study - Mahmood-ul-Hassan, Ameer Hamza; Nooz, Nehala; Tahir, Muhammad Amaz; Luqman , Meriam; Hassan Khan, Muhammad; Mohamed Khaled, Saad (Students' Supplement of Journal of Rawalpindi Medical College, 2024)
Background: Obsessive-compulsive disorder (OCD) is a psychiatric illness manifested in the form of obsessions and compulsions, and migraine is a common illness characterized by intermittent headaches that are episodic causing variable range of disability. Obsessive-compulsive disorder (OCD) is an anxiety disorder that may be associated with migraines. Objectives: This study was conducted to determine the prevalence of migraines and explore the potential association with obsessive-compulsive disorder (OCD). Materials and Methods: 220 subjects enrolled in different universities in Pakistan were approached through an online questionnaire made by using scales for assessment of Migraine (Migraine Screening Questionnaire) and obsessive-compulsive disorder (Y-BOCS). The distribution of data was determined by the Shapiro-Wilk test. Median was calculated for quantitative variables as data was nonparametric. Frequency and percentages were calculated. The p-value <0.05 was taken as statistically significant. Results: Our results determined that Migraine was significantly greater in females. Obsessive-Compulsive Disorder (OCD) was not significantly different in males and females(p-value>0.05). Cronbach’s alpha value indicated significant reliability of the Migraine Screening Questionnaire (MSQ) and Yale-Brown Obsessive Compulsion Scale (YBOCS). Conclusion: According to our study, females are more likely to suffer from migraine while OCD prevails in both genders with varying frequencies in different stages of life. Some studies suggested a three-fold increased chance of migraine in females after puberty due to hormonal imbalance.